2016
DOI: 10.1177/0194599816679952
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Olfactory Dysfunction according to Etiology and Timing of Treatment

Abstract: Objective We evaluated the severity of olfactory impairment according to risk factors, compared responses with risk factors and treatment timing, and investigated prognosis according to treatments. Study design Case series with chart review. Setting Tertiary referral center. Subjects and Methods We retrospectively reviewed medical records of patients complaining of loss of their sense of smell between January 2006 and May 2016. In total, 491 patients were included. We evaluated olfactory function using the Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 53 publications
0
45
0
1
Order By: Relevance
“…In other words, the progress of regeneration probably differs between the olfactory threshold and olfactory identification. 34) The olfactory system exhibits extraordinary plasticity because of mechanisms that have been extensively investigated at the cognitive as well as the cellular level. 35,36) The mechanisms of neural plasticity in the olfactory system are interesting, because olfactory loss is among the first symptoms of neurodegenerative disorders such as Alzheimer's disease and Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the progress of regeneration probably differs between the olfactory threshold and olfactory identification. 34) The olfactory system exhibits extraordinary plasticity because of mechanisms that have been extensively investigated at the cognitive as well as the cellular level. 35,36) The mechanisms of neural plasticity in the olfactory system are interesting, because olfactory loss is among the first symptoms of neurodegenerative disorders such as Alzheimer's disease and Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of olfactory dysfunction is quite varied, including postviral, post‐traumatic, and idiopathic loss of smell. Unfortunately, with these etiologies, the likelihood of spontaneous recovery is generally poor, with only approximately one‐third of people regaining function and the duration of loss negatively correlating with recovery rate . Treatment for olfactory dysfunction is also limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the mean duration of olfactory impairment in patients who underwent olfactory training was approximately 3 months. Kim et al 22 reported that better treatment outcomes were achieved in PIOD patients who started olfactory training less than 1 month after olfactory loss. Therefore, we concluded that immediate olfactory training might show better results in COVID-19 infection-associated OD.…”
Section: Discussionmentioning
confidence: 99%